Weakly hydrated anions bind to polymers but not monomers in aqueous solutions - Rogers, Bradley A; Okur, Halil I; Yan, Chuanyu; Yang, Tinglu; Heyda, Jan; Cremer, Paul S (Nature chemistry, 2022)
Weakly hydrated anions help to solubilize hydrophobic macromolecules in aqueous solutions, but small molecules comprising the same chemical constituents precipitate out when exposed to these ions. Here, this apparent contradiction is resolved by systematically investigating the interactions of NaSCN with polyethylene oxide oligomers and polymers of varying molecular weight. A combination of spectroscopic and computational results reveals that SCN- accumulates near the surface of polymers, but is excluded from monomers. This occurs because SCN- preferentially binds to the centre of macromolecular chains, where the local water hydrogen-bonding network is disrupted. These findings suggest a link between ion-specific effects and theories addressing how hydrophobic hydration is modulated by the size and shape of a hydrophobic entity.